PLD2 regulates microtubule stability and spindle migration in mouse oocytes during meiotic division - Liu, Xiaoyu; Liu, Xiaoyun; Chen, Dandan; Jiang, Xiuying; Ma, Wei (PeerJ, 2017)
Phospholipase D2 (PLD2) is involved in cytoskeletal reorganization, cell migration, cell cycle progression, transcriptional control and vesicle trafficking. There is no evidence about PLD2 function in oocytes during meiosis. Herein, we analyzed PLD2 expression and its relationship with spindle formation and positioning in mouse oocyte meiosis. High protein level of PLD2 was revealed in oocytes by Western blot, which remained consistently stable from prophase I with intact germinal vesicle (GV) up to metaphase II (MII) stage. Immunofluorescence showed that PLD2 appeared and gathered around the condensed chromosomesafter germinal vesicle breakdown (GVBD), and co-localized with spindle from pro-metaphase I (pro-MI) to metaphase I (MI) and at MII stage. During anaphase I (Ana I) to telophase I (Tel I) transition, PLD2 was concentrated in the spindle polar area but absent from the midbody. In oocytes incubated with NFOT, an allosteric and catalytic inhibitor to PLD2, the spindle was enlarged and center-positioned, microtubules were resistant to cold-induced depolymerization and, additionally, the meiotic progression was arrested at MI stage. However, spindle migration could not be totally prevented by PLD2 catalytic specific inhibitors, FIPI and 1-butanol, implying at least partially, that PLD2 effect on spindle migration needs non-catalytic domain participation. NFOT-induced defects also resulted in actin-related molecules’ distribution alteration, such as RhoA, phosphatidylinosital 4, 5- biphosphate (PIP2), phosphorylated Colifin and, consequently, unordered F-actin dynamics. Taken together, these data indicate PLD2 is required for the regulation of microtubule dynamics and spindle migration toward the cortex in mammalian oocytes during meiotic progression.
Keywords: Meiosis; Oocyte; Microtubule stability; PLD2; Cofilin; Actin; PIP2; RhoA; Spindle positioning